GENERATOR LISTRIK 100 WATT PUTARAN RENDAH UNTUK PEMBANGKIT LISTRIK TENAGAAIR DAN ANGIN MIKRO : DISAIN, PERENCANAAN DAN PEMBUATAN - Suhardi, Diding (Jurnal Gamma, 2010)
The more and more expensive oils from fosil to end in price electric energy more expensivebecause almost all electric station still use fosil fuel, imposible to happenes because stock of fosilfuel more and more small and no renewable again. Energy source drawer for to multiply is electricenergy from nature renewable energy exercise sun energy, win energy and water energy, and moresmall scala, and obstacle stock small generator for water energy and win energy with small scalawith low turn not to be available.In research make to design, planning and making small generator 100 watts with low turning300 rpm, for produce electric power 2,4 kWh/ unit/ day.